Sewage sludge management in a sewage treatment plant - Królik, Dariusz; Wypych, Przemysław; Kostecki, Jakub (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Sewage sludge produced in municipal sewage treatment plants, because of its physicochemical and sanitary properties, is a serious threat to the environment. In order to neutralize it, various methods of processing are used, which directly affect the quantity and quality of produced sewage sludge, which in the final stage can be used naturally. Properly managed sludge management is presented on the example of a sewage treatment plant, conducting the methane fermentation process with the production of biogas.
Keywords: sewage sludge; biogas; sewage treatment plants; osady ściekowe; biogaz; oczyszczalnia ścieków